2022
DOI: 10.1111/jan.15527
|View full text |Cite
|
Sign up to set email alerts
|

Leadership and care in nursing research: A bibliometric analysis

Abstract: Aim: This study aimed to analyse the study focus, thematic trends and evolution of studies on the leadership and care in nursing by using a bibliometric analysis.Design: Descriptive and bibliometric analyses were employed. Methods:The study universe included 3558 articles on the leadership and care in the Web of Science (WoS) database. The data analysis and graphical presentation were conducted using Bibliometrix Package in R software.Results: Within the scope of the study, articles published by 10,255 authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 49 publications
0
9
0
Order By: Relevance
“…Hot topics characterize major problems in a certain field, and they allow researchers to develop an insight into the research trends [12]. The keyword analysis conducted in this study revealed that "job satisfaction" and "burnout" emerged as hot topics about nurses' psychological empowerment.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Hot topics characterize major problems in a certain field, and they allow researchers to develop an insight into the research trends [12]. The keyword analysis conducted in this study revealed that "job satisfaction" and "burnout" emerged as hot topics about nurses' psychological empowerment.…”
Section: Discussionmentioning
confidence: 82%
“…(4) Emerging or declining themes: clusters in the lower left quadrant are themes represent clusters with few and weak links with other themes [11,12].…”
Section: B Data Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Bibliometric methods, through content and citation analyses of scholarly publications, essentially aim to identify streams of literature within a broad or more specialized subject area, including the nursing research field in particular (Ellegaard & Wallin, 2015). While alternative methods such as literature reviews may be used to search, organize and synthesize scholarly production in a particular subject area, the strength of the bibliometric approach, apart from its systematicity and its transparency, lies in its ability to uncover the relational, structural and temporal aspects of established or emerging research streams (Kantek et al, 2022). No ethical approval is needed for this type of study.…”
Section: Me Thodsmentioning
confidence: 99%
“…Over time, there have been many discussions of issues in the field of nursing leadership. In a bibliometric analysis, Kantek et al (2023) identified important data regarding nursing leadership and care. According to the study, the topics addressed on the subject are more focused on patient safety, job satisfaction, teamwork and nurse retention.…”
Section: Introductionmentioning
confidence: 99%